Radon - occurrence and impact on the health - Małgorzata M. Dobrzyńska; Aneta Gajowik; Kamil Wieprzowski (National Institute of Public Health - National Institute of Hygiene, 2023)
Radon is noble, monatomic, radioactive, heavier than the air gas. It is colorless, odorless, tasteless. It exists in natural environment as a result of the decay of radium, and emits mainly alpha radiation and less beta radiation. Residential radon concentrations vary widely by geographic area. The higher concentration of radon is expected globally in the grounds where uranium, radium and thoron are present. Radon may gather in caves, tunnels, mines as well as in other lowestlying spaces, such as basements, and cellars. In accordance with Atomic Law (2000), the reference level for the average annual concentration of radioactive radon in rooms intended for human habitation is 300 Bq/m3. The most dangerous damages caused by ionizing radiation i.e. radon and its derivatives are changes to DNA, which may disturb the functions of cells and in the consequence lead to induction of cancer of respiratory tract, mainly of lungs and also leukaemia. So, the main consequence of exposure to high amount of radon are cancers of respiratory system. Radon enters the human organism mainly through inhaled atmospheric air. Moreover, radon significantly increased a risk of induction cancer in smokers and vice versa, smoking promotes the development of lung cancer after the exposure to radon and its derivatives. Radon may also have beneficial effect on the human body. Therefore it is used in medicine; mainly in radonbalneotherapy i.e. bath treatments, rinsing the mouth and inhalation. Beneficial effects of radon confirms the validity of the theory of radiation hormesis, which assumes that low doses of radiation may stimulate the repair of DNA damage by activation of protective mechanisms, which neutralize free radicals.